Designing Monetary and Fiscal Policy in Low-Income Countries - Martijn, Jan (Occasional Papers; Occasional Paper ;, 2006)
Macroeconomic outcomes in low-income countries (LICs) have improved markedly in recent years, but important questions remain regarding possible adjustments in the design of IMF-supported programs in such countries. This paper draws on a review of the literature as well as the experience of 15 LICs that have attained some degree of macroeconomic stability to discuss, for example, the appropriate target range for inflation in shock-prone LICs; whether countries should use fiscal space to cut excessive tax burdens, reduce high debt levels, or raise public spending; and how the effectiveness of public expenditures can be improved.